Study and comparison of air pollution in three stations of Pokhara valley - Pandey, Santosh; Basnet, Kailash; Subedi, Pramod; Subedi, Aabiskar; Sapkota, Santosh (Himalayan Physics, 2024)
In recent years, air pollution has become a pressing global challenge. Nepal is no exception, facing increasing air pollution as rapid urbanisation, a surge in vehicles, poor vehicle management, infrastructure development, and industrial growth have significantly degraded air quality across many cities. This review explores the escalating air pollution in Nepal by analysing recent trends in Pokhara Valley. Using available aerosol data from 2018 to 2020, this study provides a detailed assessment of air quality and its detrimental health impacts in Pokhara. The analysis draws on data from three monitoring stations to assess PM2.5 and PM10 concentrations, evaluate compliance with air quality standards, and examine pollution distribution across the valley. In Pokhara, PM2.5 over all three stations is found to be high during winter, especially during (January-February) when air quality exceeds (AQI>100) healthy levels. In contrast, the monthly average data for PM10 is seen (AQI<100) under safer limits despite some noticeable rise in winter seasons. Among these three stations, the DHM station recorded maximum and minimum Air quality index values of 243 in December 2019 and 11 in August and September 2018, respectively. The objectives include identifying key pollution sources and their impact on air quality and offering insights into the region's current state of air pollution. The findings of this study can play a crucial role in informing future planning and policy-making, offering data to help devise effective strategies to mitigate air pollution. These insights contribute to national and global efforts to improve air quality and reduce environmental pollution.